Calculation of S-values for Technetium-99m in the DIGIMOUSE voxel phantom using Monte Carlo simulations. (July 2022) - Teles, P.; Antunes, J.; Gómez-Ros, J.M.
Abstract: A correct dosimetry of radionuclides in small animals is of great importance for the development of radiopharmaceuticals. The objective of this study was to determine the S-values for 99m Tc in the DIGIMOUSE voxel phantom, using the MIRD methodology and Monte Carlo simulations. For benchmarking, self-absorbed fractions in the kidneys were determined, for photons and electrons, using a monoenergetic source in the energy range 10 keV to 4 MeV. Obtained results showed a deviation of 5% or less for photons and for electrons up to 1 MeV when compared to results to other studies found in the literature. After validation, a source of 99m Tc was defined in various source organs to determine the S-values. After this, the self-absorption S-values were fitted as a function of the inverse of the mass yielding extremely accurate results. It can be shown that the electronic S-values follow a 1/m function with a multiplication constant of 12.9 keV which corresponds to the average energy of the emitted electrons of 13.9 keV. Furthermore, a qualitative analysis of the crossfire S-values is provided. The main affected organs by crossfire radiation are the stomach, the spleen, and the pancreas, whereas the heart and the lungs are mainly affected by each other, respectively. The results obtained for the S-values were also compared with previously published results. The differences obtained between the different studies can be justified by differences in the choice of density and stoichiometric composition of the organs of DIGIMOUSE relative to other mouse voxel phantoms. Finally, the obtained results can be useful for researchers who need to perform dosimetric calculations of novel radiopharmaceuticals labelled with 99m Tc. Highlights: Calculation of 99mTc S-values in a mouse phantom. Interest for professionals working in preclinical nuclear medicine. Modelling self-absorption S-values for varying organ sizes. Need for the development of a reference mouse phantom.